Presence of Marphysa disjuncta (Polychaeta: Eunicidae) in the Mediterranean Sea - KURT SAHIN, G.; CINAR, M.E. (Mediterranean Marine Science, 2009)
An individual belonging to the eunicid polychaete species Marphysa disjuncta Hartman, 1961 was collected on muddy substratum at 100 m deep in Fethiye Bay (Levantine Sea, eastern Mediterranean). This species is new to the Mediterranean fauna. It closely resembles to Marphysa bellii, a native species, but it lacks compound falcigers and has unidentate subacicular hooks. This species was only reported from the eastern and western Pacific Ocean and could have been introduced to the Mediterranean Sea via ballast waters of vessels.